2017
DOI: 10.20959/wjpps20176-9307
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Smart Characteristics of Smart Polymers

Abstract: ABSTARCTImportance of smart polymers is raising day by day as these polymers under go large reversible, physical or chemical changes in response to small changes in environment so, they are also known as "stimuli

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results in table 5 reveal that the methods are successful for the determination of drugs and that the excipients in the dosage forms do not interfere. The results were compared to the available validated reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] methods on each drug and the results agree well with the claim and also are in agreement with the results obtained by the literature method. Statistical evaluation results were used to test the accuracy by Student's t-test and precision by F-test (Table 6) which revealed no significant change was observed between the literature method and proposed method at the 95 % confidence level with reference to accuracy and precision.…”
Section: Application To Formulationssupporting
confidence: 82%
See 2 more Smart Citations
“…The results in table 5 reveal that the methods are successful for the determination of drugs and that the excipients in the dosage forms do not interfere. The results were compared to the available validated reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] methods on each drug and the results agree well with the claim and also are in agreement with the results obtained by the literature method. Statistical evaluation results were used to test the accuracy by Student's t-test and precision by F-test (Table 6) which revealed no significant change was observed between the literature method and proposed method at the 95 % confidence level with reference to accuracy and precision.…”
Section: Application To Formulationssupporting
confidence: 82%
“…Thorough literature studies acknowledged that various methods are reported for the quantification of BSN both in finished dosage forms and biological fluids, such as Spectrophotometry [3], RP-HPLC [4,5] and HPTLC [6].…”
Section: Fig 1: Structure Of Bosentanmentioning
confidence: 99%
See 1 more Smart Citation